Planning And Designing Schools With Disabilities Basic Education With Behavioral Architecture Approach In Surabaya - Supriyadi Supriyadi (Publikasi Indonesia, 2023)
Disabled schools are an opportunity for educational services that must be optimally emphasized and highlighted for children with disabilities, have significant implications for special/special education, and joint education centers or joint learning must have programs and systems, namely inclusive education, responsibility/accountability and learning accessibility, positive behavior and collaboration. Students with disabilities still do not understand and can get an education, because there are still many obstacles or obstacles related to physical human activity. With problem-solving methods as well as developing the ability to analyze and read symptoms critically every movement that can occur around. Behavior in children with special needs varies depending on the needs required, in a building and especially in architectural spaces can be realized by architectural elements. Designed based on the need for function and to accommodate children with disabilities to get early/basic education with future interests to be able to care for themselves. The role and guidance of parents is also expected to be a major consideration and an important factor. So, it is hoped that the Planning and Design of Schools with Disabilities in Basic Education with the Behavioral Architecture Approach in Surabaya will become one of the reference considerations in designing schools with disabilities in basic education